Dehydrogenative Silylation of Alkenes for the Synthesis of Substituted Allylsilanes by Photoredox, Hydrogen‐Atom Transfer, and Cobalt Catalysis - Yu, Wan‐Lei; Luo, Yong‐Chun; Yan, Lei; Liu, Dan; Wang, Zhu‐Yin; Xu, Peng‐Fei (Angewandte Chemie International Edition, 2019)
A synergistic catalytic method combining photoredox catalysis, hydrogen‐atom transfer, and proton‐reduction catalysis for the dehydrogenative silylation of alkenes was developed. With this approach, a highly concise route to substituted allylsilanes has been achieved under very mild reaction conditions without using oxidants. This transformation features good to excellent yields, operational simplicity, and high atom economy. Based on control experiments, a possible reaction mechanism is proposed. A synergistic catalytic method of combining photoredox catalysis, hydrogen‐atom transfer, and proton‐reduction catalysis for the dehydrogenative silylation of alkenes was developed. The reaction features high regioselectivity, excellent tolerance of functional groups, wide substrate scope, and mild reaction conditions. Moreover, this oxidant‐free system offers a cleaner and more efficient method beyond traditional catalysis, which requires either stoichiometric or excess amounts of oxidants.